Development of Android-Based Mobile Learning Media Using ADDIE Model on Static Fluid Topics for High School 11th Grade Students - Mutmainnah, Besse; Amni, Zurratul; Wahyudi, Muh (Universitas Islam Negeri (UIN) Mataram, 2023)
This research and development study aimed to create a mobile learning application based on the Android platform to facilitate the teaching and learning of static fluid concepts. The ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model was employed as the framework for the research methodology. The data collection instruments included validation questionnaires completed by subject matter experts, media experts, physics teachers, and students. These were administered during small-group and large-group trials conducted with 11th-grade science students at MAN 1 Lotim. The end product was an Android-based learning app that received an overall good rating with a total score of 82. Evaluation by media experts deemed it good, with a score of 60 out of a maximum of 75. Physics teachers who validated the app rated it as very good/effective with a score of 52. During the large group trial with students, the app gained a high score of 1759, averaging 4.31 which falls into the very interesting category. Based on the validation results and feedback obtained, it can be concluded that the Android-based mobile learning application developed in this study is suitable, effective, and practical to be utilized as an instructional tool for teaching static fluid concepts to high school 11th-grade students in physics education programs.